ISOLATION, IDENTIFICATION AND ANTAGONISTIC ACTIVITY OF MARINE ACTINOMYCETES FROM COASTAL REGIONS OF CUDDALORE DISTRICT, TAMILNADU - KOLANJIYAPPAN, DINESH KUMAR; JAGADHEESHKUMAR, VIGNESHWARI; KANDASAMY, SENTHILKUMAR PALANI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The chemical synthesized antibiotics used against different bacterial infectious disease .The prolonged usage of antibiotics had side effects. Actinomycetes are having lot of potential pharmaceutical applications. Bioactive compounds derived from marine actinomycetes having less side effects and having potential applications. Sediment samples collected from Pichavaram, TS pettai, Parangipettai, Ponanthittu and MGR Thittu coastal areas Chidambaram, Tamil Nadu. The collected samples were pretreated using calcium carbonate (CaCO3) and air dried for three to seven days. Samples are serially diluted for spread plate technique. In this technique, totally 25 actinomycetes isolated for further analysis. All the isolates were screened for antagonistic activity against disease-causing clinical bacterial pathogens such Klebsiella pneumonia, Shigella dysentriae, Salmonella typhi, Streptococcus pyogenes, Streptococcus pnemoniae, Salmonella paratyphi, Vibrio parahaemolyticus, Serratia marcescens, and Enterococcus harmaechei.Among this 25 isolates, the isolate TSP1 showing better antagonistic activity against all the bacterial pathogens. The potential strain TSP1 were identified by morphological, microscopical, biochemical, and SEM analytical characterization. Based on the results, the TSP1 isolate are identified as Streptomyces sp. The current research focuses on actinomycetes that have antagonistic activity and create bioactive secondary metabolites that cure several infectious diseases. The aim and objective of this present study is isolation of marine actinomycetes from sediment samples and evaluated antagonistic activity against bacterial pathogens.